2010
DOI: 10.1016/j.fertnstert.2010.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Autoantigens in ovarian autoimmunity associated with unexplained infertility and premature ovarian failure

Abstract: Study Objective-To identify ovarian autoantigens associated with ovarian autoantibodies.Design-Hypothesis generating prospective study. Setting-Urban infertility referral centers and academic research institution.Patients-74 patients with infertility, 19 patients with premature ovarian failure, 16 healthy control women. Interventions-None. Main outcome measures-Identification of autoantigens.Results-In order to identify major antigens for ovarian autoimmunity, 74 sera from women with unexplained infertility we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 57 publications
2
40
0
4
Order By: Relevance
“…Previous reports have identified PDIA3 by MS in the mammalian ovary tissue and [65] in embryo culture media [66]. Its function in the reproductive systems has not yet been elucidated; however, it could be suggested that it includes cell growth and death.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have identified PDIA3 by MS in the mammalian ovary tissue and [65] in embryo culture media [66]. Its function in the reproductive systems has not yet been elucidated; however, it could be suggested that it includes cell growth and death.…”
Section: Discussionmentioning
confidence: 99%
“…19 Prematür ovaryan yetmezliği ya da açıklanamayan infertilitesi olanlarda selenyum bağlayıcı protein-1'e karşı otoantikorlar saptanmıştır. 20 Melatonin bir başka antioksidan madde olup, ortamdaki serbest radikalleri temizleyerek antioksidan enzimleri indüklemektedir. Kontrollü ovaryan stimülasyon sırasında melatonin takviyesinin oositi oksidatif stresten koruyup IVF sonuçlarını iyileştirmesi beklenebilir.…”
Section: Anti̇oksi̇danlarunclassified
“…It has been demonstrated that 21 of 110 women with autoimmune POF express this autoantibody, whereas 60 control subjects proved negative. Aldehyde (retinal) dehydrogenase 1A1 (ALDH1A1) and selenium-binding protein 1 (SBP1) are identified as unique autoantigenic targets associated with unexplained infertility (Edassery et al, 2010).…”
Section: Anti-ovarian Antibodies and Infertilitymentioning
confidence: 99%